Assessment of antenatal care services and nutritional status of pregnant women-a cross sectional study in tribal blocks of Nanded district - Gattani, Prakash L.; Nakel, Mahavir P.; Butte, Rajabhau S.; Bansode, Abhijit L.; Jogdanad, D. G.; Pawade, Govind (International Journal Of Community Medicine And Public Health, 2023)
Background: Maternal and child healthcare is one of the eight basic components of primary healthcare (PHC) in the declaration of Alma-Ata. There is an excellent system of primary health care services for the delivery of maternal and child health services through a network of sub-centres and PHC centres in rural India. Aim and objectives of the study to assess antenatal care (ANC) care services and MCH schemes given to tribal women in Nanded district. Objectives- To study status of ANC care services among tribal ANC mothers. To assess various schemes associated with mother and child health in tribal area. Methods: Study design was a cross-sectional study. Study conducted at tribal blocks in Nanded district. Sampling and sample size: Convenient purposive sampling was used. Study population was 100 ANC mothers of tribal blocks in Nanded district. Results: Total number of families belonging to BPL category were 67% and families belonging to APL were 33%. Maximum of 60% were housewives, 39% of ANC mothers were working in the farm, while only 1 ANC mother was Govt. servant. Conclusions: Addressing the physical and financial barriers of tribal women to access maternal health services, catering the services to their socio-cultural needs, building in trust between beneficiaries in the community and health care delivery system should be the priority.